2015
DOI: 10.1177/1010539515598835
|View full text |Cite
|
Sign up to set email alerts
|

Level of Physical Activity in Population Aged 16 to 65 Years in Rural Kerala, India

Abstract: Kerala is a state in India with a high prevalence of cardiovascular diseases and diabetes. In order to control these diseases, the prevalence of modifiable risk factors such as low physical activity need to be studied. For this a cross-sectional study was conducted to assess the level of physical activity among 240 residents aged between 15 and 65 years in Kulappuram, a village in north Kerala. Low level of physical activity was seen in 65.8% of the study participants. The average duration of moderate to vigor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…13 In the majority of studies, there was a significant association between the age and physical activity levels. 5,6,12,18,20 In our study, along with a significant association, we also found that the trend for sedentary activity was decreasing as the age increases and was significant. This is a physiological process that as the age increases, the physical capacity of individual decreases and thus the physical activity level.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…13 In the majority of studies, there was a significant association between the age and physical activity levels. 5,6,12,18,20 In our study, along with a significant association, we also found that the trend for sedentary activity was decreasing as the age increases and was significant. This is a physiological process that as the age increases, the physical capacity of individual decreases and thus the physical activity level.…”
Section: Discussionsupporting
confidence: 79%
“…Various studies have been conducted across the world to assess the physical activity levels among all age groups. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] This study is an attempt to focus on the physical activity levels and its correlates among adults of central India.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of low-level physical activity among Mongolian adults, 10.9% in 2005 and 27.2% in 2013, was similar to that in a study from Thailand, which reported a proportion of 26.0% in 2014 23 ) and lower than those reported in studies from Bangladesh 24 ) , India 25 ) , and Vietnam 21 , 26 ) . Physical activity time of Mongolian adults was similar to the study from Vietnam 21 ) and longer than those of Bangladesh 24 ) , India 25 ) . The comparatively high level and longer time of physical activity of Mongolian adults were attributed to long leisure physical activity time compared to other study subjects 27 ) .…”
Section: Discussionsupporting
confidence: 79%
“…Employee workers were more likely to engage in leisure physical activity than were self-employed workers in the present study. Previous studies indicated affordability and accessibility affected leisure-time physical activity among white-collar workers 25 , 36 , 37 , 38 ) . To our knowledge, there is no previous record of physical activity facilities in Mongolia; however, a national report published in 2017 on leisure-time physical activity facilities reported that Mongolia has 98 sport complex in the country and 18 swimming pools, 58% of sport complex and 77% of swimming pools are located in urban area 39 ) .…”
Section: Discussionmentioning
confidence: 96%
“…The study concluded that more behavioral change activities are warranted to increase recreational physical activity. 10 Noncommunicable diseases are preventable through various health education and promotional activities and the reduction the sociobehavioral risk factors, such as physical inactivity, tobacco use, harmful use of alcohol, and unhealthy diet and other lifestyle changes. Further research is needed to develop more innovative preventive strategies, early detection, improved health care, and timely services and also to evaluate the effectiveness of population-based interventions to prevent NCDs from escalating in Asia.…”
Section: Smentioning
confidence: 99%